2010
DOI: 10.1088/1755-1315/12/1/012107
|View full text |Cite
|
Sign up to set email alerts
|

Impact of startup scheme on Francis runner life expectancy

Abstract: Francis runners are subject to complex dynamic forces which might lead to eventual blade cracking and the need for corrective measure. Damage due to cracks in runner blades are usually not a safety issues but might generate unexpected down time and high repair cost. Avoiding the main damaging operating conditions is often the only option left to plant operators to maximize the life expectancy of their runner. The startup scheme is one of the available parameter which is controlled by the end user and could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 1 publication
0
33
0
Order By: Relevance
“…In order to do this, Hydro-Québec decided to use the data from their measurement campaigns on Francis and propeller runners to identify and validate dynamic models that will represent the turbines behavior and enable start-up optimization. This paper follows previous work conducted at Hydro-Quebec by Gagnon et al [1][2][3], and by other researchers [4,5], on the impact of a transient operation on Francis runners, and builds on the review on fatigue damage mechanisms in hydro turbines [6].…”
Section: Introductionmentioning
confidence: 75%
“…In order to do this, Hydro-Québec decided to use the data from their measurement campaigns on Francis and propeller runners to identify and validate dynamic models that will represent the turbines behavior and enable start-up optimization. This paper follows previous work conducted at Hydro-Quebec by Gagnon et al [1][2][3], and by other researchers [4,5], on the impact of a transient operation on Francis runners, and builds on the review on fatigue damage mechanisms in hydro turbines [6].…”
Section: Introductionmentioning
confidence: 75%
“…However, operating at no-load (with just enough flow to overcome machine losses) wastes valuable water resources, while operation at low load, particularly within the so-called rough running zone, is associated with excessive machine vibration and decreased asset life and therefore should be avoided whenever possible [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, transient events often account for most of the damages sustained by hydroelectric turbines during their operation [2]. They affect the turbine lifetime both by accelerating crack propagation on the runner blades [3] and damaging the bearings. The exerted unsteady fluctuations during the transients are a challenge for the turbine designers and power plant owners because they are difficult to predict during the design stage.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that in both cases the fatigue damage increases during load variation. Gagnon et al [3] showed that the damage to a Francis runner during start-up event is significantly dependent on the start-up scheme. Houde et al, [1] directly measured the pressure fluctuations exerted on the runner blades of a propeller turbine during runaway and speed-no-load conditions.…”
Section: Introductionmentioning
confidence: 99%